PENGARUH RENDAM KAKI MENGGUNAKAN AIR HANGAT TERHADAP KECEMASAN PADA PASIEN HIPERTENSI - Dian Anggri Yanti; Tati Murni Karo-karo; Anita Sri Gandaria Purba; Junita Ika Susanti Br Ginting; Raisha Octavariny; Nurul Fernanda Williani (JURNAL PENGMAS KESTRA (JPK), 2021)
Hypertension is a condition of a person who has an increase in blood pressure above normal. Anxiety is an emotional response to a subjective assessment with a state of anxiety, worry, fear and increased emotions. Soak the feet using warm water. for the body to oxygenate body tissues for anxiety. Aim; To find out the effect of foot baths using warm water on anxiety in hypertensive patients at the Grandmed Hospital in 2020. Method; This research is an experimental research that is pre experimental design using one group prepost by using a comparison group (control) with a sample of 42 respondents while the research instrument uses a questionnaire sheet and observation sheet, using an anxiety measurement tool (HARS). Data analysis used bivariate analysis namely Paired Sample T-Test. Results; Bivariate test results with Paired Sample T-Test Test prove that there is an effect of foot bath action using warm water to reduce anxiety before and after the action is carried out proven by the value of p = 0,000 <0.05. Conclusion; there is an effect of soaking the feet using warm water on anxiety in hypertensive patient.